PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN TEKNIK MENERAN “TIUP” TERHADAP BIDAN, KADER DAN IBU HAMIL DI WILAYAH KARAWANG BARAT KABUPATEN KARAWANG - Rahayu Pertiwi; Ida Farida Handayani; A.Achmad Fariji; Imam Makhrus (Poltekkes Kemenkes Bandung, 2022)
One of the factors causing perineal tears is the way of pressing in the second stage of labor. Several studies have shown that the “Blow” breathing technique at the end of the second stage of labor is an effective method of reducing excessive pressure on the perineum. But in general, most women do the pressing technique with the Valsalva technique, which is a strong and long pressing technique that has the risk of large perineal tears and fetal asphyxia. The results of the author's survey in the Karawang district obtained data from 20 postpartum mothers, 17 of whom experienced a perineal tear during childbirth, and they said they were still using the traditional menan technique (Valsava). This community empowerment activity is to improve the knowledge and skills of midwives, cadres and pregnant women regarding the